Interaction of opioid with insulin/IGFs signaling in Alzheimer's disease - Salarinasab, Sadegh; Salimi, Leila; Alidadiani, Neda; Shokrollahi, Elhameh; Arzhanga, Pishva; Karbasforush, Saedeh; Marofi, Faroogh; Nasirzadeh, Mahdieh; Rahbarghzi, Reza; Nourazarian, Alireza; Nikanfar, Masoud (Journal of Molecular Neuroscience, 2020)
Alzheimer's disease is associated with biochemical and histopathological changes characterized by molecular abnormalities. Due to the lack of effective treatments for Alzheimer's disease, many attempts have been made to find potential therapies to reduce or even return neuronal loss after disease initiation. Alzheimer's disease is also touted as type III diabetes, showing an association with insulin signaling. The large distribution of the insulin receptor on the cell surface and its regulatory role in the central nervous system suggests that the pathogenesis of Alzheimer's disease could be ascribed to insulin signaling. The interference of opioids, such as morphine with insulin signaling pathways, is thought to occur via direct crosstalk between the signaling pathways of the insulin receptor and the mu-opioid receptor. In this review article, we discuss the possible crosstalk between the mu-opioid receptor and insulin signaling pathways. The association of these two signaling pathways with Alzheimer's disease is also debated.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Alzheimer’s disease; Insulin/IGFs system; MAPK/ERK signaling pathway; Opioids; PI3K/AKT signaling pathway